THE IMPACT OF THE APPLICATION OF LOCAL WISDOM IN LEARNING MATERIALS ON THE MOTIVATION OF STUDENTS IN ELEMENTARY SCHOOLS - Andri Sungkowo; Hudson Sidabutar; Munkizul Umam Kau (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2024)
The study aims to explore the impact of the application of local wisdom in the learning material on the motivation of students in primary schools. In today's educational context, there is a growing awareness of the importance ofining and integrating local values and practices into the formal education system as a means of supporting a learning process that is more relevant and meaningful to students. This study investigates how the integration of local wisdom into the curriculum can motivate students to participate more in the learning process as well as improve their understanding of the lessons delivered. The research uses a method of literary review, which involves the collection and analysis of various literary sources relevant to the research topic. These resources include journal articles, textbooks, research reports, and online resources related to local wisdom, contextual learning, and student learning motivation. Research results show that the integration of local Wisdom into the learning material has a positive effect on the motivation of students in elementary schools. Students tend to feel more connected to the materials taught when they can identify elements of their own local culture and environment. This makes it easier for students to understand the abstract concepts taught, while enriching them with wider knowledge of the environment in which they live. Furthermore, research finds that the use of local wisdom in education also contributes to the development of student pride and cultural identity. From a pedagogical point of view, teaching using local wisdom-based content and methods shows the potential to encourage active and participatory learning, which directly boosts learning motivation.